2021
DOI: 10.1055/a-1728-1347
|View full text |Cite
|
Sign up to set email alerts
|

Undescribed C-Glycosylflavones from Corn Silk and Potential Anti-inflammatory Activity Evaluation of Isolates

Abstract: Phytochemical investigation of corn silk resulted in isolation and characterization of four flavone C-glycosides, chrysoeriol 6-C-β-oliopyranosyl-7-O-β-D-glucopyranoside (1), 3′-methoxycassiaoccidentalin A (2), chrysoeriol 6-C-β-boivinopyranosyl-7-O-β-D-glucopyranoside (3), and ax-4"-OH-3′-methoxymaysin (4), a triterpenoid, friedelin (5), two sterols, (22E)-5,8-epidioxyergosta-6,22-dien-3β-ol (6) and 6β-hydroxystigmasta-4,22-diene-3-one (7), and a mixture of β-sitosterol and stigmasterol. Compounds 1 and 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, in modern clinics, corn silk is applied to treat various diseases, such as nephritis, acute and chronic pneumonia, diabetes, hypertension, and edema [6]. In addition, many modern pharmacological activities, such as antihypertension activities [7], lowering blood lipids [8], anti-inflammatory activities [9], anti-urolithiasis activities [10], anti-oxidant activities [11], protecting the liver [12], and other effects [13] have been verified in previous studies.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, in modern clinics, corn silk is applied to treat various diseases, such as nephritis, acute and chronic pneumonia, diabetes, hypertension, and edema [6]. In addition, many modern pharmacological activities, such as antihypertension activities [7], lowering blood lipids [8], anti-inflammatory activities [9], anti-urolithiasis activities [10], anti-oxidant activities [11], protecting the liver [12], and other effects [13] have been verified in previous studies.…”
Section: Introductionmentioning
confidence: 95%
“…Modern studies showed that corn silk owned diversiform ingredients, including flavonoids [17,18], polysaccharides [19,20], polyphenols [21], amino acids [22], and other components [23], among which flavonoids with antiinflammatory [24,25], antioxidant [26], and other helpful biological activities [27] were especially abundant. Our previous study has revealed that the main constituents absorbed into the blood of corn silk were flavonoids [28], indicating flavonoids may be the nominated material basis of pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%